The problem with renewables. (1st August 2022) - Edwards, Peter; Dobson, Peter; Owen, Gari
Abstract : Peter Edwards, Peter Dobson and Gari Owen say that net-zero targets can only be met if renewable energy can be stored cost-effectively.